Synthesis, characterization and anticancer activity of mono- and dinuclear Ni(II) and Co(II) complexes of a Schiff base derived from o-vanillin - Bahron, H; Khaidir, SS; Tajuddin, AM; Ramasamy, K; Yamin, BM (Pergamon-Elsevier Science Ltd, 2024)
Indexed by WOS/ Scopus